ANALYSIS OF SCIENCE LITERACY COMPONENTS IN GRADE XII BIOLOGY TEXTBOOKS ON GROWTH AND DEVELOPMENT MATERIAL - Adlini, Miza Nina; Tarigan, Fanny Adha Chyntia; Pranriska, Iftitah; Miftahuddin; Anggriani, Syaprina; Syafitri, Wanda (REVIEW OF MULTIDISCIPLINARY EDUCATION, CULTURE AND PEDAGOGY, 2023)
Scientific literacy is a form of scientific knowledge and skills possessed by someone to identify a question, acquire new knowledge, explain scientific phenomena. This study aims to analyze the contents of biology textbooks in scientific literacy on growth and development material in class XII SMA/MA. The research was conducted using a qualitative approach with content analysis method. Analysis of the scientific literacy component was carried out after obtaining book data. Data collection in research on the analysis of components of scientific literacy in class XI biology textbooks was carried out by means of surveys, observation and documentation. Percentage results between comparisons of 2 science literacy books, the first book with 18 points found at a percentage of 53% (Very good category) while the second book with 16 points found at a percentage of 47% (Good category). The two books do not have very much differences in content, it only takes a good understanding to digest the contents of each book's purpose in presenting its material.